Euro-Mediterranean statistics on n short-term indicators = Bulletin de Conjoncture Euro-Mediterraneenne - European Union; Statistical Office of the European Communities (Belgium Office of the European Union, 1997)
Euro-Mediterranean Bulletin on short-term indicators is a publication of Eurostat which aims to meet the information needs of all those concerned with the economic development of the signatory countries of the Barcelona Declaration
Title on cover #2 (1998): Euro-Mediterranean statistics
Keywords: General Statistics - Europe; STATISTICS; MEDITERRANEAN COUNTRIES; EUROPEAN COMMUNITIES